The role of oral vitamin D in several skin diseases - Adelia, Astri; Wibawa, Larisa Paramitha; Sampurna, Adhimukti T; Budianti, Windy K; Zubier, Farida (Journal of General - Procedural Dermatology and Venereology Indonesia, 2017)
Vitamin D has many benefits for body and skin health. One of them is to regulate the immune system, both cellular and humoral. The pathogenesis of many skin diseases is associated with disturbance in regulation of cellular immune system. Research on the relationship between blood level of vitamin D and several diseases in dermatology is currently very advanced. Oral vitamin D is known to have many functions that play a role in the pathogenesis of several diseases of the skin. Therefore, its current use as a primary or supplemental therapy has been widely studied. Knowledge on various skin diseases with indication of oral vitamin D use is important to be understood, especially in association with some chronic diseases requiring long-term therapy. The effects of using oral vitamin D analogues are minimal, but hypervitaminosis D might cause uncomfortable symptoms for patients. Therefore, it is important to understand and regulate the amount of doses of oral vitamin D supplements prescribed.